2011
DOI: 10.1021/bi201362z
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Kinetic Stability of Hyperstable Proteins via Time-Dependent SDS Trapping

Abstract: Globular proteins are usually in equilibrium with unfolded conformations, whereas kinetically stable proteins (KSPs) are conformationally trapped by their high unfolding transition state energy. Kinetic stability (KS) could allow proteins to maintain their activity under harsh conditions, increase a protein's half-life, or protect against misfolding-aggregation. Here we show the development of a simple method for quantifying a protein's KS that involves incubating a protein in SDS at high temperature as a func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…This method prevents re-association or aggregation of dissociated monomer. Dissociation rate constants k d for wt and L82A were indistinguishable (Table 1), and the rate constant for wt is consistent with published data (19). Thus, the lack of tetramer dissociation for L82A incubated with Aβ is not due to an increase in L82A stability relative to wt.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This method prevents re-association or aggregation of dissociated monomer. Dissociation rate constants k d for wt and L82A were indistinguishable (Table 1), and the rate constant for wt is consistent with published data (19). Thus, the lack of tetramer dissociation for L82A incubated with Aβ is not due to an increase in L82A stability relative to wt.…”
Section: Resultssupporting
confidence: 90%
“…We previously showed that L110A and L82A mutations did not cause a loss of secondary, tertiary, or quaternary structure in TTR (13). We tested whether these mutations caused a more subtle effect on tetramer stability by measuring dissociation at high temperature using the S-Trap method (19). This method prevents re-association or aggregation of dissociated monomer.…”
Section: Resultsmentioning
confidence: 99%
“…This is also illustrated very well in a more recent study by the Colón group 13 . Hyperstable proteins such as superoxide dismutase or transthyretin are incubated with SDS at elevated temperatures such as 70 o C, and samples can then be removed and monitored by SDS-PAGE which can also quantify the amount of folded and unfolded protein.…”
Section: Studying Kinetically Stable Proteins: Using Sds For Conformasupporting
confidence: 76%
“…We have shown that hyper-stable (i.e., kinetically stable) proteins are resistant to SDS (Manning and Colon 2004;Xia et al 2012) and have developed a diagonal two-dimensional (D2D) SDS-PAGE method to identify such proteins at a proteomics level (Xia et al 2007). In this study, we used human plasma as a model system and carried out D2D SDS-PAGE to determine whether the plasma of older age adults contains higher amounts of SDS-resistant aggregates (SRA) than the plasma of younger adults.…”
Section: Introductionmentioning
confidence: 99%